Aggregates of nonmuscular myosin IIA in erythrocytes associate with GATA1- and GFI1B-related thrombocytopenia - Zaninetti, Carlo; Rivera, Jose’; Vater, Leonard; Ohlenforst, Sandra; Leinøe, Eva; Böckelmann, Doris; Freson, Kathleen; Thiele, Thomas; Makhloufi, Houssain; Rath, Matthias; Eberl, Wolfgang; Wolff, Martina; et al. (Journal of thrombosis and haemostasis, 2024)
The transcription factor GATA1 is an essential regulator of erythroid cell gene expression and maturation and is also relevant for platelet biogenesis. GATA1-related thrombocytopenia (GATA1-RT) is a rare X-linked inherited platelet disorder (IPD) characterized by macrothrombocytopenia and dyserythropoiesis. Enlarged platelet size, reduced platelet granularity, and noticeable red blood cell anisopoikilocytosis are characteristic but unspecific morphological findings in GATA1-RT. To expand the investigation of platelet phenotype of patients with GATA1-RT by light- and immunofluorescence microscopy on a blood smear. We assessed blood smears by light- and immunofluorescence microscopy after May-Grünwald Giemsa staining using a set of 13 primary antibodies against markers belonging to different platelet structures. Antibody binding was visualized by fluorescently labeled secondary antibodies. We investigated 12 individuals with genetically confirmed GATA1-RT from 8 unrelated families. While confirming the already known characteristic of platelet morphology (platelet macrocytosis and reduced expression of markers for α-granules), we also found aggregates of nonmuscular myosin heavy chain II A (NMMIIA) in the erythrocytes in all individuals (1-3 aggregates/cell, 1-3 μm diameter). By systematically reanalyzing blood smears from a cohort of patients with 19 different forms of IPD, we found similar NMMIIA aggregates in the red blood cells only in subjects with GFI1B-related thrombocytopenia (GFI1B-RT), the other major IPD featured by dyserythropoiesis. Aggregates of NMMIIA in the erythrocytes associate with GATA1-RT and GFI1B-RT and can facilitate their diagnosis on blood smears. This previously unreported finding might represent a novel marker of dyserythropoiesis assessable in peripheral blood.